IMPACT OF E-COMMERCE GROWTH ON LOCAL RETAIL MARKETS: A STUDY ON CHITRADURGA, KARNATAKA - B, Shiva Kumar; Pasha, Mujammil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
E-commerce has emerged as a key driver of economic transformation worldwide. In India, the rapid penetration of e-commerce platforms is creating significant shifts in business practices and consumer behavior. However, this phenomenon poses both opportunities and challenges, particularly for small and traditional retail markets in semi-urban areas. This paper investigates the effects of e-commerce growth on local retail businesses in Chitradurga, Karnataka. It explores how local merchants adapt to online platforms, examines barriers to digital adoption, and identifies trends in changing consumer preferences. The findings suggest that while e-commerce is driving retail innovation, local businesses must strategically integrate offline and online models to remain competitive. Recommendations include policy interventions, training programs, and the development of hybrid retail ecosystems to ensure sustainable growth in the region.